2018
DOI: 10.4028/www.scientific.net/msf.925.280
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Tensile Properties of High Silicon Ductile Iron

Abstract: The casting processes are characterized by complex relationships between predictors and responses. It is the fundamental understanding of these complex relationships that often involves hundreds of factors, which improves quality without losing productivity and raising cost. In this work, cast solid solution strengthened ferritic spheroidal graphite irons GJS-500-14 and GJS-600-10 (EN 1563:2012) have been evaluated. These materials offer stronger components with good machinability owing to their even hardness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The metallurgical parameters or mechanisms that are significant for tensile strength remain elusive. For GJS-600-10 HSI, the use of adapted runners and filters was paramount in achieving the required elongations [8]. Conversely, the impact data in Figure 1 indicate that mimicking the elongation-only approach entails significant risk.…”
Section: Effect Of Elongation and Impact Properties On High Silicon Ductile Ironmentioning
confidence: 99%
See 1 more Smart Citation
“…The metallurgical parameters or mechanisms that are significant for tensile strength remain elusive. For GJS-600-10 HSI, the use of adapted runners and filters was paramount in achieving the required elongations [8]. Conversely, the impact data in Figure 1 indicate that mimicking the elongation-only approach entails significant risk.…”
Section: Effect Of Elongation and Impact Properties On High Silicon Ductile Ironmentioning
confidence: 99%
“…Based on the elongation data to the left in Figure 1, GJS-500-14 was produced with 3.5 to 4.5% Si and GJS-600-10 was produced with 4 to 5% Si if the specification limits stipulated in EN1653 were followed [6]. HSI castings with 4 to 5% Si partially adhering to GJS-600-10 were nearly independent of key casting process parameters like nodularity, nodule count and carborn eqivalent, CE, when determining, ultimate tensile stress (UTS or R m ), yield strength (R p ) and elongation (A%) [7,8]. The metallurgical parameters or mechanisms that are significant for tensile strength remain elusive.…”
Section: Effect Of Elongation and Impact Properties On High Silicon Ductile Ironmentioning
confidence: 99%
“…Despite the highest content of silicon (4.55-5.25% Si), the third group is characterized by an intermediate Px level (1.52-1.72), due to the higher incidence of presence of the minor elements. Then it could be concluded that the favorable effect of high silicon content in ferrite formation allows the tolerance of higher amounts of pearlite and carbide stabilizing elements in the chemical composition of the High-Si ductile cast irons [1,2,14,15].…”
Section: Chemical Compositionmentioning
confidence: 99%
“…An improvement of the machinability, maintaining or even improving the mechanical properties of the ferritic-pearlitic SGI, was the starting point for the first investigations on these high Si cast irons. 1,2 The European Standard EN-1563:2012 introduced three new grades of fully ferritic SGI, characterized by a higher Si content that induces a strengthening of the ferrite by solid solution: Si solid solution strengthened full ferritic ductile iron grades (SSF DI). The guidance values for the chemical composition are presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%